Wake force excited by ultrarelativistic electron bunch in rectangular waveguide with periodic perturbed walls - Opanasenko, A. (Вопросы атомной науки и техники, 2008)
А perturbation method for calculation of wakefields in a periodic waveguides with periodic perturbed walls is developed. The analytical formulas for a transverse component of an alternating wake force were derived.